2015
DOI: 10.1177/1358863x15573839
|View full text |Cite
|
Sign up to set email alerts
|

The validity of ICD codes coupled with imaging procedure codes for identifying acute venous thromboembolism using administrative data

Abstract: The purpose of this study was to evaluate the accuracy of using a combination of International Classification of Diseases (ICD) diagnostic codes and imaging procedure codes for identifying deep vein thrombosis (DVT) and pulmonary embolism (PE) within administrative databases. Information from the Alberta Health (AH) inpatients and ambulatory care administrative databases in Alberta, Canada was obtained for subjects with a documented imaging study result performed at a large teaching hospital in Alberta to excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 22 publications
2
80
0
Order By: Relevance
“…However, automated identification of PPS variables largely depends on the International Classification of Diseases 9th/10th Revision (ICD-9/10) coding. Given that diagnostic coding may be inaccurate or omit relevant conditions, [14][15][16][17][18][19] the performance of automated algorithms is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, automated identification of PPS variables largely depends on the International Classification of Diseases 9th/10th Revision (ICD-9/10) coding. Given that diagnostic coding may be inaccurate or omit relevant conditions, [14][15][16][17][18][19] the performance of automated algorithms is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, administrative database codes to confirm a diagnosis of DVT may not always be reliable. Alotaibi et al found that administrative data was 75.2% sensitive and 95.8% specific for DVT, 25 with other studies showing similar findings. 26,27 The true incidence and clinical significance of DVT/EHIT are unable to be determined without evaluating clinic notes and radiographic files, which are unavailable in claims database.…”
Section: Discussionmentioning
confidence: 61%
“…First, we included over 2.2 million people with over 17 000 000 person-years of observation using comprehensive data linked from province-wide and federal administrative databases. We used a previously validated algorithm for identifying VTE events 6,7 and our overall IR for VTE is virtually identical to that reported in two recent Canadian studies in Quebec and Alberta. 11,12 We used a validated algorithm to determine ethnicity 5 derived from multiple comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this study we used algorithms comprising both diagnostic and procedural codes (i.e, imaging studies codes) with appropriate sensitivity and specificity to try to decrease the possibility of misclassification. 6,7,14 In spite of this, there is a possibility that a number of patients might have been missed or erroneously included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation